Intra-host diversity of hepatitis B virus during mother-to-child transmission: the X gene may play a key role in virus survival in children after transmission - Li, Yanjie; Shen, Chenguang; Yang, Liuqing; Yang, Yang; Wang, Miao; Li, Shanqin; Chen, Feng; Yang, Min; Peng, Ling; Ma, Jinmin; Duan, Zhongping; Li, Liqiang; et al. (Archives of virology, 2020)
Mother-to-child transmission of hepatitis B virus (HBV) is the main route of transmission in Asia, and characterization of HBV quasispecies is needed to further understand virus evolution and adaptation. To understand changes in HBV during mother-to-child transmission, we enrolled nine pairs of mothers and children in the study, including a set of twins. Three groups were infected with HBV genotype C, and six groups were infected with HBV genotype B. The full-length HBV genome was amplified by PCR from serum samples before antiviral treatment, the whole viral genomes from each pair were sequenced, and the complexity and diversity of the quasispecies were analyzed. The entropy of transmitted HBV in children was found to be lower than their mothers, suggesting that there was a bottleneck effect during HBV transmission from the mother to the child. Selective evolution was shown by calculating πN and πS in the whole genomes, and the highest values were obtained for the X gene, which plays a role in viral replication and immune escape. All genotype C patients and only one genotype B pair had a πN/πS greater than 1 ratio, indicating that positive selection had occurred. In addition, quasispecies were found to be different between the twin children despite having the same mother, indicating that virus evolution is host-specific.